Electronic Books (E-books): Current Trends and Future Directions - Connaway, Lynn Silipigni (DESIDOC Journal of Library & Information Technology, 2003)
As a greater number of electronic resources becomes available, retrieving relevant and authoritative information has become progressively more challenging and time consuming. Locating relevant information in a timely manner is critical for both the researcher and the information professional. Electronic books (eBooks) are one way to enhance the digital library with global 24-hours-a-day and 7-days-a-week access to authoritative information, and they enable users to quickly retrieve and access specific research material easily, quickly, and effectively. It is crucial to not only provide these electronic resources, but to integrate them into library systems to streamline library operations, as well as promote user adoption. As an eBook provider, netLibrary, a division of OCLC, Online Computer Library Center, has been involved in the selection, cataloguing, and distribution of eBooks. Library users are able to remotely search, locate, and checkout eBooks from the library’s online public access catalogs (OPACs). As with any new opportunity, new challenges emerge and utilising the internet to deliver book content is no exception. Integrating eBooks into the digital library has created challenges and opportunities for librarians, publishers, and eBooks providers. http://dx.doi.org/10.14429/dbit.23.1.3585